Nursing of a patient with pain caused by acute mastitis treated with manual lymphatic drainage of the breast combined with auricular acupoint sticking and pressing therapy (手法按摩排乳联合耳穴贴压治疗1例急性乳腺炎初起疼痛的护理体会) - FAN Dongpan (范东盼); CHEN Hong (陈宏); JIA Ruijing (贾瑞晶); XU Jingjin (徐京巾); ZHANG Jing (张敬); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the effect of manual lymphatic drainage of the breast combined with auricular acupoint sticking and pressing therapy in the treatment of breast pain and related nursing measures for a patient with acute mastitis during lactation. Under the guidance of scientific nursing assessment and Traditional Chinese medicine syndrome differentiation, manual lymphatic drainage of the breast combined with auricular acupoint sticking and pressing therapy was carried. Comprehensive interventions such as diet nursing and emotion care were also implemented during the treatment. (本文总结手法按摩排乳联合耳穴贴压治疗1例哺乳期急性乳腺炎初起疼痛的效果和护理经验。护理人员先进行科学的护理评估, 在中医辨证施护理论指导下, 采取手法按摩排乳联合耳穴贴压干预, 同时配合饮食、情志、生活等常规护理干预, 患者疼痛症状明显缓解, 红肿消退。)